Digitizing Croatian Latin Writers - Jovanović, Neven, filolog (2008)
Croatian Latin literature is usually taken to mean the body of works written in Latin both in the region that is today Croatia, and by authors of Croatian origin. The corpus of such literature comprises - according to a recent bibliographical survey - 3685 authors and 5994 (printed) titles, written from Middle Ages until modern times. The Croatiae auctores Latini, a digital collection in the making, aims to make accessible as many of these authors and works as possible. But, how should it be done? A collection wants to be used ; therefore, it has to attract its users, enabling them to do something not possible without the collection. Moreover, if a collection which wants to be used offers material that is exotic, almost unknown - the collection also has to provide as many background information as possible. Finally, if a collection is built with limited resources, it has to rely on its main asset: the community of its users (along the lines of commons-based peer production). So the Croatiae auctores Latini digital collection should include not only texts in its three "aggregate states" of digitisation (as images, as text only, and encoded in different levels). The collection should also include search facilities and secondary literature. To maximally engage its user community, the collection should be open - making it easy to correct, enhance, or add texts and other resources, giving due credit to each contributor - and flexible enough to be used even for the purposes the designers have not envisaged. To conclude, I will sketch what we currently have and what we do not have, pointing also to the initiatives and institutions - Croatian and foreign - which we see as natural allies of the planned collection.